Real-time rendering - Möller, Tomas, 1971-; Haines, Eric, 1958-; Hoffman, Naty (CRC Press, Taylor and Francis Group, 2018)
Real-Time Rendering combines fundamental principles with guidance on the latest techniques to provide a complete reference on three-dimensional interactive computer graphics. It will help you increase speed and improve image quality and learn the features and limitations of acceleration algorithms and graphics APIs. This latest fourth edition has been updated to include a chapter on virtual reality and augmented reality and covers new topics such as visual appearance, global illumination, and curves and curved surfaces. It is for anyone serious about computer graphics who wants to learn about algorithms that create synthetic images fast enough that the viewer can interact with a virtual environment.